Verrucous carcinoma: a clinical case report and a review of treatment methods (International Journal of Scientific Research and Management (IJSRM), 2019)
Verrucous carcinoma (VC) is a rare pathological finding. The etiology of the disease remains unclear. Smoking, alcohol consumption, human papilloma virus (HPV), poor oral hygiene are considered the main etiologic factors. It affects people at the age between 50 and 80-year-old with a slight male prevalence. Once developed, the tumor grows slowly and might be wrongly taken as a benign neoplasm. However, it can be locally destructive and invasive. The most effective method of treatment is a total surgical removal of the tumor. In the following we present a clinical case report of a 46-year-old female with VC.